Process for forming an insulating material concrete wall panel

By forming an interface treatment layer of diatomaceous earth particles and alkaline colloidal silica aqueous dispersion on the surface of the insulation board, the problems of drying retention and hydration continuity of the interface between the insulation board and cement-based concrete are solved, and the continuity of the interface bonding is improved.

CN123040185APending Publication Date: 2026-11-06SHANDONG HUISHENG CONSTR TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611468576.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In the existing technology, it is difficult to balance the dry and fixed state of the interface material before pouring and the hydration continuity of the interface after pouring in the interface bonding between the insulation board and the cement-based concrete.

Method used

An interface treatment layer containing diatomaceous earth particles and alkaline colloidal silica aqueous dispersion is formed on the surface of the insulation board. After coating and drying, a structure with a consolidation part, connecting inter-particle pores and exposed diatomaceous earth surface is formed, ensuring that the interface material remains dry and fixed before pouring, and forming continuous contact with the hydration products of cement paste after concrete pouring and curing.

Benefits of technology

It improves the continuous bonding between the insulation board and the cement-based concrete interface, solves the problem of the difficulty in simultaneously achieving the drying and fixation of the interface material and the subsequent interface hydration and bonding, and enhances the continuity of the interface bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123040185A_ABST
    Figure CN123040185A_ABST
Patent Text Reader

Abstract

The application discloses a thermal insulation material concrete wallboard forming process, relates to the forming technology field of thermal insulation concrete composite wallboard for fabricated buildings, and adds diatomite particles containing amorphous silicon dioxide phase into an alkaline colloidal silicon dioxide water dispersion liquid to be dispersed, so that an interface treatment slurry is obtained; the interface treatment slurry is coated on a concrete contact surface of a molded polystyrene foam plastic plate and is dried, so that a thermal insulation board with an interface treatment layer is obtained; the interface treatment layer has a consolidated part located at a diatomite particle and a thermal insulation board surface contact part and an adjacent diatomite particle contact part, and has a connected pore formed by a particle gap and leading to a concrete side and a diatomite particle exposed surface area directly connected with the connected pore; then, cement-based concrete is cast and is maintained. The process considers the drying holding of the interface material before casting and the interface hydration connection after casting, and improves the continuous combination degree of the interface of the thermal insulation board and the cement-based concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of molding technology for thermally insulated concrete composite wall panels for prefabricated buildings, and in particular to a molding process for thermally insulated concrete wall panels. Background Technology

[0002] Thermal insulation concrete wall panels are typically prefabricated in factories. In this process, insulation boards are laid in advance on a mold, and then cement-based concrete is poured on the concrete contact side of the insulation boards. After compaction, curing, and demolding, a wall panel is formed that combines the insulation layer and the concrete layer. To improve the interfacial bonding between the organic insulation board and the cement-based concrete, existing processes usually apply an interface treatment material to the surface of the insulation board, allowing it to participate in the interfacial connection between the insulation board and the cement paste during the concrete pouring process.

[0003] For the interface treatment method of pre-setting active inorganic particles, the interface treatment material needs to be dried and stably attached to the surface of the insulation board before concrete pouring to meet the requirements of insulation board laying, storage and transportation. The solid phase formed during the drying process is prone to form a continuous cover on the particle surface and particle gaps, which reduces the surface of active particles and the interconnected space formed by particle gaps, and restricts the contact and subsequent hydration connection between the post-poured cement-based concrete and the pre-set inorganic particles.

[0004] Therefore, how to balance the dry and fixed state of the interface material before pouring with the hydration continuity of the interface after pouring is a technical problem that needs to be solved in the molding process of thermal insulation concrete wall panels. Summary of the Invention

[0005] This invention provides a molding process for thermal insulation material concrete wall panels, comprising: Diatomaceous earth particles containing amorphous silica phase are added to an alkaline colloidal silica aqueous dispersion for dispersion to obtain an interface treatment slurry. An interface treatment slurry is applied to the concrete contact surface of a molded polystyrene foam board and dried to obtain an insulation board with an interface treatment layer. The interface treatment layer contains a solidified portion at the contact point between diatomaceous earth particles and the surface of the insulation board, as well as a solidified portion at the contact point between adjacent diatomaceous earth particles, and adjacent solidified portions separated by particle gaps. The interface treatment layer has interconnecting pores formed by particle gaps and leading to the concrete-facing side of the interface treatment layer. The interface treatment layer also contains exposed surface areas of diatomaceous earth particles that are directly connected to the interconnecting pores. The insulation board with the interface treatment layer is laid on the formwork, with the interface treatment layer facing the concrete pouring side, and cement-based concrete is poured on the side of the interface treatment layer. After the wall panel is poured, it is cured in the formwork and then cured again after demolding. The interface treatment layer after curing contains a region of hydrated calcium silicate that is in continuous contact with the hydration products of cement paste in cement-based concrete, thus obtaining a thermal insulation concrete wall panel.

[0006] Preferably, the dried interface treatment layer contains open pores on the diatomaceous earth particles, the open pores are connected to the outer surface of the particles, their openings are kept open, and they are connected to the side of the interface treatment layer facing the concrete through the connecting pores.

[0007] Preferably, the cured interface treatment layer has open pores of hydrated calcium silicate distributed on the surface of the pore wall and in the adjacent pore cavities.

[0008] Preferably, the contact portion contains a liquid bridge observed during the drying process, and a solidified portion is observed at the original liquid bridge location after the drying endpoint is reached.

[0009] Preferably, the interface treatment slurry is composed of diatomaceous earth particles and an alkaline colloidal silica aqueous dispersion.

[0010] Preferably, after curing, there is a continuous hydrated calcium silicate region between the interface treatment layer and the cement paste of the cement-based concrete. The continuous hydrated calcium silicate region is distributed sequentially in the contact area between the diatomite particles and the surface of the insulation board or the contact area between adjacent diatomite particles, the surface area of ​​the diatomite particles, and the cement paste area of ​​the cement-based concrete, and the hydrated calcium silicate in the above-mentioned adjacent areas is in continuous contact with each other.

[0011] Preferably, the coating and drying of the interface treatment slurry are completed before the insulation board enters the wall panel forming mold. After the insulation board has been dried, it is stored and transported and then laid on the wall panel forming mold. Cement-based concrete is poured on one side of the interface treatment layer and cured.

[0012] The beneficial effects of this invention are as follows: This invention solves the problem of simultaneously maintaining the dryness and firmness of the interface material and subsequent interface hydration and bonding by forming an interface treatment layer on the surface of the insulation board, which has a consolidation part, connecting the pores between particles and the exposed diatomaceous earth surface. This allows the interface material to remain dry and firm before pouring, and forms a hydrated calcium silicate region that is in continuous contact with the hydration products of the cement paste after concrete pouring and curing. This improves the continuous bonding between the insulation board and the cement-based concrete interface. Attached Figure Description

[0013] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 This is a schematic diagram of the molding process of the thermal insulation material concrete wall panel in Example 1; Figure 2 This is a three-dimensional reconstruction image of the interface sample after drying using X-ray microtomography in Example 1. Figure 3 This is a secondary electron imaging image of the interface sample after drying in Example 1; Figure 4 The image shows the Raman spectral density of the interface specimen from Example 1 after 28 days. Figure 5 This is a BSE imaging image of the interface specimen from Example 1 at 28 days. Figure 6 This is an EDS element distribution diagram of the 28-day interface specimen from Example 1. Figure 7 This is a comparison diagram of the liquid bridge formation state in Example 1 and the solidification state after drying at the same coordinate, wherein, Figure 7 (a) in the diagram shows the liquid bridge formation state at the contact point of adjacent diatomite particles. Figure 7 (b) in the diagram shows the consolidation state at the same coordinate position after reaching the unified drying endpoint of the group. The dashed circle indicates the corresponding observation position. Detailed Implementation

[0015] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0016] Unless otherwise described in the embodiments, Examples 1-3 and Example 5 use molded polystyrene foam boards of the same specifications, refined diatomaceous earth from the same source and batch, alkaline colloidal silica aqueous dispersion of the same specifications, cement, natural medium sand, crushed stone and polycarboxylate-based high-performance water-reducing agent. Example 4 uses diatomaceous earth from another mineral source, and the chemical composition, phase, particle size, BET specific surface area and particle pore structure of the diatomaceous earth used are described in Example 4.

[0017] refer to Figures 1 to 7 The molded polystyrene foam board used has dimensions of 600 mm × 600 mm × 50 mm and an apparent density of 20.5 kg / m³. 3 The surface formed by sawing without aluminum foil, plastic film or mortar covering is selected as the concrete contact surface. Before interface treatment, clean compressed air is used to remove the floating dust on the concrete contact surface. The concrete contact surface is not ground, flame treated or pre-coated with other interface materials.

[0018] The refined diatomaceous earth used in Examples 1-3 and Example 5 had a SiO2 mass fraction of 88.9%, a water content of 0.76%, a D10 of 7.8 μm, a D50 of 24.7 μm, a D90 of 53.9 μm, and a BET specific surface area of ​​31.2 m². 2 / g; Phase detection was performed using a Cu target X-ray diffractometer, and a broad diffuse peak corresponding to amorphous silica was observed in the range of 2θ from 20° to 30°, while a quartz diffraction peak was detected at the diffraction angle corresponding to crystalline quartz; under a scanning electron microscope, openings extending from the outer surface of the particles to the inside of the particles could be observed.

[0019] The colloidal silica aqueous dispersion used was an alkaline silica sol, with water as the dispersion medium. The solid mass fraction was 20.6%, the average particle size was 12.4 nm, the pH at 25 °C was 9.31, and the density was 1.128 g / cm³. 3 The dynamic viscosity is 4.2 mPa·s, and the colloidal silica was not surface modified with organic polymers.

[0020] Each embodiment prepared an interface treatment slurry according to the amount of alkaline silica sol and diatomaceous earth described in the corresponding embodiment. The alkaline silica sol was added to a mixing container and stirred at 500 r / min. The diatomaceous earth was divided into three equal parts by mass and added to the alkaline silica sol in sequence. The interval between the addition of two adjacent parts of diatomaceous earth was 60 s. After the third part was added, stirring was continued for 5 min. After stirring was stopped, the mixture was allowed to stand for 3 min. The resulting interface treatment slurry was coated within 30 min after preparation.

[0021] The interface treatment slurry was first applied along the length of the insulation board using a short-nails roller, and then along its width, covering the entire concrete contact surface. The ambient temperature for slurry preparation and application was 25±2 ℃, and the relative humidity was 52±5%. Each insulation board was weighed before and after application, and the difference between the two weighing values ​​was taken as the actual mass of slurry used. The wet coating amount was calculated based on a treatment area of ​​0.36 m². The unit area load of dry solids of silica sol and the unit area load of diatomaceous earth were calculated based on the actual proportion of alkaline silica sol and diatomaceous earth added to this batch of slurry.

[0022] The interface treatment substrates for the drying witness test specimens, the interface test specimens after drying, the liquid bridge observation test specimens, and the 28-day interface specimens were all made of the same batch of molded polystyrene foam as the corresponding wall panel insulation board. The same contact surface cleaning method and the same numbered interface treatment slurry were used for coating as the corresponding wall panel. The slurry coating quality of each synchronous test specimen was calculated based on the interface treatment area of ​​the test specimen and the measured wet coating amount of the corresponding numbered wall panel, so that the synchronous test specimens and the corresponding wall panels used the same wet coating amount per unit area.

[0023] The drying witness test samples were 50 mm × 50 mm molded polystyrene foam test pieces. After coating, they were placed in an environment of 25 ± 2 ℃ and 52 ± 5% relative humidity, with the treated surface facing upwards, for natural drying. Starting from 20 h of drying, 5 drying witness test samples were weighed every 2 h. When the difference between two consecutive weighing values ​​of the same drying witness test sample was not greater than 0.004 g, the time corresponding to the last weighing was recorded as the drying endpoint of the sample. The latest time of reaching the drying endpoint among the 5 drying witness test samples in the same group was used as the unified drying endpoint of the wall panel insulation board and the corresponding test sample in the same group.

[0024] The cement used was P·O 42.5 ordinary Portland cement, with a specific surface area of ​​354 m² / kg, an initial setting time of 171 min, and a final setting time of 228 min. The fine aggregate was natural medium sand with a fineness modulus of 2.68 and an apparent density of 2620 kg / m³. The coarse aggregate was continuously graded crushed stone with a particle size of 5–20 mm and an apparent density of 2690 kg / m³. The solid mass fraction of the polycarboxylate-based high-performance water-reducing agent was 20.3%.

[0025] For each cubic meter of cement-based concrete, 385 kg of cement, 158 kg of water, 712 kg of natural medium sand, 1065 kg of 5-20 mm continuously graded crushed stone, and 3.47 kg of polycarboxylate-based high-performance water-reducing agent are weighed and set aside. During preparation, the natural medium sand and crushed stone are first put into a forced mixer and dry-mixed for 30 seconds, then cement is added and mixing is continued for 30 seconds. Subsequently, 158 kg of water and 3.47 kg of polycarboxylate-based high-performance water-reducing agent are added to the mixer and mixing is continued for 120 seconds to obtain cement-based concrete. After each batch of cement-based concrete is mixed, the slump is tested, and the corresponding wall panels and 28-day interface specimens are poured within 30 minutes after the mixing is completed.

[0026] In each embodiment, five independent insulation boards were used to form the wall panels. Each wall panel corresponded to a batch of independently prepared interface treatment slurry and a batch of independently mixed cement-based concrete. The insulation boards that had reached the uniform drying endpoint of their respective groups were laid in a 600 mm × 600 mm mold, with the interface treatment surface facing the concrete pouring side. A 100 mm thick layer of the corresponding batch of cement-based concrete was poured on one side of the interface treatment surface and compacted with a vibrating table for 30 seconds.

[0027] After drying, the interface specimens were directly used for interface structure testing after reaching the unified drying endpoint of the corresponding group; the liquid bridge observation specimens were observed under a microscope from the time the interface treatment slurry was applied; after the interface treatment layer reached the unified drying endpoint of the corresponding group, the 28-day interface specimens were poured with cement-based concrete of the same batch as the wall panel with the same number on one side of the interface treatment surface, with a concrete thickness of 100 mm, and were treated with the same vibration compaction and curing conditions as the corresponding wall panel.

[0028] In the implementation conditions requiring 28-day interface testing, one 28-day interface specimen is prepared from each of the first, second, and third batches of interface treatment slurry, and then poured with cement-based concrete of the same batch number from the first, second, and third batches respectively to form three independent 28-day interface specimens.

[0029] After the wall panels and 28-day interface specimens were cast, they were placed in an environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for 48 hours to cure in the mold. After demolding, they continued to be cured under the same temperature and humidity conditions for 28 days. The time unit d in this article means day, and 1 day is calculated as 24 hours.

[0030] Unless otherwise stated, for each implementation condition, three independent dried interface samples or three independent 28-day interface specimens from different batches of interface-treated slurry were used for corresponding testing, and multiple observation areas in the same specimen were used as the internal testing locations of the specimen.

[0031] The SiO2 mass fraction of diatomaceous earth was determined by X-ray fluorescence spectrometry, the moisture content was determined by drying and weighing at 105 °C, the particle size was determined by laser particle size distribution and D10, D50 and D90 were recorded, the BET specific surface area was determined by nitrogen adsorption, and the phase composition was detected by Cu target X-ray diffraction with a scanning range of 2θ of 5° to 70° and a scanning speed of 2° / min. The solid mass fraction of alkaline silica sol was determined by drying and weighing at 105 °C, the average particle size of the colloid was determined by dynamic light scattering, and the pH was determined at 25 °C.

[0032] Scanning electron microscopy uses secondary electron imaging to observe the surface and interface morphology of particles, and backscattered electron imaging to observe the cross-sectional morphology and different composition regions. These are referred to as SEM secondary electron images and BSE images, respectively. Elemental composition and spatial distribution of elements are detected using an energy-dispersive X-ray spectrometer (EDS) that is paired with the scanning electron microscope.

[0033] After drying, the interface sample is first subjected to X-ray microtomography and the three-dimensional reconstruction data and spatial coordinates are saved. When it is necessary to perform three-dimensional structure and cross-sectional morphology correspondence detection, the X-ray microtomography is completed before cutting, grinding and other destructive sample preparation. After the three-dimensional scan is completed, the positioning section is prepared according to the saved coordinates, and then SEM secondary electron imaging, BSE imaging and EDS detection are performed.

[0034] The term "consolidation zone" as used in this article refers to the solid connection region located at the contact position between the diatomaceous earth particles and the surface of the insulation board or at the contact position between adjacent diatomaceous earth particles after the interface treatment slurry has dried, and which can continuously cross the contact boundary and connect the solids on both sides of the contact in SEM secondary electron images or BSE images.

[0035] After drying, the observation field of each interface sample is continuously moved along the interface direction from the middle of the interface treatment surface to find areas that can completely show the contact position between diatomite particles and the surface of the insulation board and the contact position between adjacent diatomite particles. After confirming the consolidation part at both types of contact positions, the area between adjacent consolidation parts is observed. When there is a continuously identifiable interparticle space between adjacent consolidation parts, it is recorded that the sample has adjacent consolidation parts separated by interparticle gaps.

[0036] The exposed surface area referred to in this article is the surface area of ​​diatomaceous earth particles that, after the interface treatment layer has dried, can still be directly identified in SEM secondary electron images or positioning sections, including the original outer contour, pores, or surface texture of the diatomaceous earth particles, and is directly connected to the gaps between the particles.

[0037] Interparticle connectivity pores were confirmed using X-ray microtomography. In the three-dimensional reconstruction data, the pore space was traced layer by layer from the interface treatment layer towards the concrete. The interparticle gaps that could continuously enter the interior of the diatomite particle layer from this side without being interrupted by the solid structure were recorded as interconnected interparticle pores.

[0038] For each independently dried interface sample, a continuous pore path that can be traced from the interface treatment layer towards the concrete to the surface of the diatomite particles is determined in the three-dimensional reconstruction data. The three-dimensional coordinates of the position where the path meets the diatomite particles are recorded, and a positioning section is prepared according to the coordinates. When the boundary of the pore in the positioning section directly reaches the exposed surface area, it is recorded that the sample has a direct spatial connection between the pore and the exposed surface of the diatomite particles.

[0039] The openings were confirmed using a combination of SEM secondary electron imaging and X-ray microtomography reconstruction data. In the SEM secondary electron imaging, when there were identifiable openings on the outer surface of the diatomite particles and cavities extending into the particles could be continuously observed from the openings, they were recorded as openings. In the three-dimensional reconstruction data, when the pores inside the particles could be continuously entered through the openings into the inter-particle pores and continued to be traced to the side of the interface treatment layer facing the concrete, the opening was recorded as being connected to the concrete side.

[0040] Liquid bridges were continuously observed using a fixed sample stage microscopic imaging device. Images were acquired every 30 seconds after the interface treatment slurry was coated. When a local liquid phase with a curved liquid-gas interface and continuous connection between the solids on both sides appeared at the contact position between the diatomite particles and the surface of the insulation board, or at the contact position between adjacent diatomite particles, this position was recorded as a liquid bridge and its coordinates were saved. After the sample continued to dry to the unified drying endpoint of its group, the same contact position was re-observed according to the saved coordinates. When a consolidation part that meets the aforementioned definition exists at the position, the correspondence between the liquid bridge state during the drying process and the consolidation part state after the drying endpoint at this contact position was recorded.

[0041] When it is necessary to obtain a comparative image of the liquid bridge state and the solidified state after drying, select an observation position with complete storage coordinates that can show the contact position and its adjacent area. Acquire an image at this position when the liquid bridge is formed, and re-acquire an image at the same position according to the stored coordinates after the group reaches the same drying endpoint to form a comparative result at the same coordinate position.

[0042] After the 28-day interface specimens reached the specified age, a smooth interface section containing the insulation board, interface treatment layer, and cement paste was prepared. Before the conductive treatment, the section was first used for optical positioning and Raman detection, and the coordinates of each Raman detection position were saved. After the Raman detection was completed, subsequent sample preparation required for SEM secondary electron imaging, BSE imaging, and EDS detection was performed. The Raman results were correlated with the SEM, BSE, and EDS results based on the saved coordinates.

[0043] Microscopic Raman detection was performed using a 532 nm laser and a 100x objective lens. The laser power on the sample surface was controlled below 3 mW, and the detection wavenumber range was 200–1400 cm⁻¹. -1 Spectral resolution no greater than 2 cm -1 Before each batch of tests, calibration was performed according to the wavenumber calibration procedure that comes with the Raman instrument. The reference position and the position to be tested for the same specimen were subjected to the same acquisition conditions.

[0044] For each 28-day interface specimen, five Raman reference spectra were obtained from a continuous cement paste region in the optical image on the cement-based concrete side, and the position coordinates were saved. After Raman detection, BSE images were used to confirm that the location belonged to the cement paste region. At least four common major silicate characteristic bands and their peak ranges were recorded in the five reference spectra, and the peak range was used as the Raman reference range for the specimen.

[0045] The effective interface length referred to in this article is the interface length in a 28-day cross-section specimen where the insulation board, interface treatment layer, and cement paste are all continuously identifiable along the interface direction and can be located and detected by Raman, BSE, and EDS.

[0046] For each 28-day interface specimen, a fixed observation area of ​​250 μm × 200 μm was set at positions of 20%, 35%, 50%, 65%, and 80% of the effective interface length. The 250 μm direction was perpendicular to the interface between the insulation board and the cement-based concrete. A total of 15 fixed observation areas were formed by the three independent specimens.

[0047] Within each fixed observation area, one Raman positioning position is first determined in the particle contact area, the diatomite particle surface area, and the cement slurry area based on the cross-sectional optical image without conductive treatment. Raman detection is performed at the three positions and the coordinates are saved. After all Raman detections are completed, SEM secondary electron imaging, BSE imaging, and EDS surface scanning are performed on the same fixed observation area. Based on the saved coordinates, it is confirmed that the three Raman positioning positions belong to the particle contact area, the diatomite particle surface area, and the cement slurry area, respectively.

[0048] When the solid hydration products in the BSE image can be continuously traced from the particle contact area through the diatomite particle surface area to the cement paste area, and the EDS surface scan shows that Ca and Si are co-distributed on the corresponding continuous path, and the main silicate characteristic spectral peaks of the above three Raman positioning positions all fall within the Raman reference range of the specimen, the observed area is recorded as a continuous hydrated calcium silicate region; if BSE confirms that any Raman positioning position does not belong to the corresponding specified area, the observed area is not recorded as meeting the above judgment conditions.

[0049] The presence of hydrated calcium silicate in the open pores was confirmed using a combination of Raman, BSE, and EDS methods. Open pores that could continuously identify the outer surface of particles, pore openings, pore walls, and adjacent cavities were selected from the cross-section of the 28-day interface specimen. Raman positioning positions were determined on the pore wall surface or adjacent cavities, and their coordinates were saved. After Raman detection, BSE observation and EDS surface scanning were performed at the same coordinates. When solid hydration products, Ca and Si co-distributed, and the peak positions of the main silicate characteristic spectral bands fell within the Raman reference range of the specimen at the same location, the presence of hydrated calcium silicate in that open pore was recorded.

[0050] Example 1 Five batches of interface treatment slurry were prepared. For each batch, 40.0 g of alkaline silica sol and 30.0 g of refined diatomaceous earth were taken, and dispersion and settling were completed under the aforementioned common conditions. Each batch yielded 70.0 g of interface treatment slurry, and each batch contained 8.24 g of dried silica sol solids. The mass ratio of dried silica sol solids to refined diatomaceous earth was 0.275:1. The first to fifth batches of interface treatment slurry were used for the first to fifth wall insulation boards and the corresponding test samples, respectively.

[0051] The actual mortar masses used for the five insulation boards were 44.92 g, 45.08 g, 44.79 g, 45.16 g, and 44.87 g, respectively, corresponding to wet coating amounts of 124.8 g / m². 2 125.2 g / m 2 124.4 g / m 2 125.4 g / m 2 and 124.6 g / m 2 The solid load per unit area for silica sol drying was 14.69 g / m². 2 14.74 g / m 2 14.65 g / m 2 14.77 g / m 2 and 14.67 g / m 2 The unit area load of refined diatomaceous earth was 53.48 g / m². 2 53.67 g / m 2 53.32 g / m 2 53.76g / m 2 and 53.42 g / m 2 .

[0052] For each of the first to fifth batches of interface treatment slurry, one dry witness sample was prepared. For the first, second and third batches of interface treatment slurry, one dry interface sample, one liquid bridge observation sample and one 28-day interface specimen were prepared separately. All synchronous samples were treated according to the measured wet coating amount per unit area of ​​the wall panel insulation board with the same number.

[0053] The drying endpoints for the first to fifth drying witness samples were 22 h, 24 h, 24 h, 26 h and 24 h, respectively. The latest one, 26 h, was taken as the unified drying endpoint in this embodiment. All five wall panel insulation boards, three dried interface samples and three 28-day interface specimens were dried to 26 h.

[0054] Three liquid bridge observation samples were continuously observed under a microscope. Liquid bridges were observed at the contact positions between diatomite particles and the surface of the insulation board, as well as at the contact positions between adjacent diatomite particles. After reaching a uniform drying endpoint of 26 h, the samples were re-observed according to the saved coordinates. In both types of contact positions, it was confirmed that there were consolidation parts corresponding to the original liquid bridge positions.

[0055] Representative control results were selected from one of the contact points between adjacent diatomaceous earth particles, as shown below. Figure 7 As shown, Figure 7 In (a) of the diagram, the dashed circle indicates a localized liquid bridge observed during the drying process of the interface-treated slurry. This bridge features a curved liquid-gas interface and continuously connects the solids on both sides of the liquid phase. After the sample continues drying to a uniform drying endpoint of 26 hours, the same location is re-observed according to the saved coordinates. The results are as follows: Figure 7 As shown in (b), a consolidation portion that continuously crosses the contact boundary and connects the solids on both sides of the contact is observed at the corresponding position.

[0056] Five batches of cement-based concrete were prepared independently. The slump of the first to fifth batches of concrete were 164 mm, 169 mm, 166 mm, 171 mm and 163 mm, respectively. The five wall panels were laid, poured and vibrated using cement-based concrete with the same number. The first to third batches of cement-based concrete were used for three 28-day interface specimens with the same number. The wall panels and interface specimens were cured for 28 days under the aforementioned common conditions.

[0057] Three independent dried interface samples were subjected to SEM secondary electron imaging, BSE imaging, and X-ray microtomography. In each sample, consolidation portions were observed at the contact points between diatomite particles and the insulation board surface, as well as at the contact points between adjacent diatomite particles. Adjacent consolidation portions separated by particle gaps were also observed. In the three-dimensional reconstruction data, it was possible to continuously trace from the interface treatment layer towards the concrete along the particle gaps into the interior of the diatomite particle layer. After preparing the positioning section according to the three-dimensional coordinates, it was confirmed that the connected pores of each sample directly reached the exposed surface area of ​​the diatomite particles.

[0058] In all three dried interface samples, open pores extending from the outer surface of the diatomaceous earth particles to the inside of the particles were observed. The three-dimensional reconstruction data confirmed the existence of open pores that enter the inter-particle interconnecting pores from the internal pores of the particles through the pore openings and continue to the interface treatment layer facing the concrete side.

[0059] Raman reference ranges were established for three 28-day interface specimens using the aforementioned Raman reference method. The peak positions of the main silicate characteristic bands of the first specimen ranged from 667 to 674 cm⁻¹. -1 and 962–977 cm -1 The second piece measures 669–675 cm. -1 and 961~979 cm -1 The third piece measures 668–675 cm. -1 and 963~978 cm -1 .

[0060] A total of 14 openings that could continuously identify the orifice, orifice wall and adjacent cavity were located in 3 28-day interface specimens. Among them, solid hydration products, Ca and Si co-distribution and main silicate characteristic bands that conform to the Raman reference range of the corresponding specimens were observed in 12 openings on the surface of the orifice wall or in adjacent cavity. These were recorded as the presence of hydrated calcium silicate in the opening.

[0061] According to the aforementioned unified testing sequence, 15 fixed observation areas of 3 28-day interface specimens were tested. Among them, 14 observation areas, after Raman positioning and subsequent BSE and EDS coordinate confirmation, met the criteria for continuous hydrated calcium silicate between particle contact area, diatomite particle surface area and cement paste area. 5, 4 and 5 observation areas of specimens 1 to 3 met the criteria, respectively.

[0062] Example 2 Five batches of interface treatment slurry were prepared. Each batch contained 32.0 g of alkaline silica sol and 30.0 g of refined diatomaceous earth, resulting in 62.0 g of interface treatment slurry per batch. Each batch contained 6.592 g of dried silica sol solids, and the mass ratio of dried silica sol solids to refined diatomaceous earth was 0.220:1.

[0063] The actual mortar masses used for the five insulation boards were 39.73 g, 39.95 g, 39.81 g, 39.88 g, and 39.69 g, respectively, corresponding to wet coating amounts of 110.4 g / m². 2 111.0 g / m 2 110.6 g / m 2 110.8 g / m 2 and 110.2 g / m 2 The solid load per unit area for silica sol drying was 11.73 g / m². 2 11.80 g / m 2 11.76 g / m 2 11.78 g / m2 and 11.72 g / m 2 The unit area load of refined diatomaceous earth was 53.40 g / m². 2 53.70 g / m 2 53.51 g / m 2 53.60g / m 2 and 53.35 g / m 2 .

[0064] For each of the first to fifth batches of interface treatment slurry, one dry witness sample was prepared. For the first, second and third batches of interface treatment slurry, one dry interface sample and one 28-day interface specimen were prepared separately. Each synchronous sample was treated according to the measured wet coating amount per unit area of ​​the corresponding numbered wall panel insulation board.

[0065] The drying endpoints for the first to fifth drying witness samples were 22 h, 24 h, 22 h, 24 h and 24 h, respectively. In this embodiment, the drying endpoint was uniformly set at 24 h.

[0066] Five batches of cement-based concrete were mixed independently. The slump of the first to fifth batches of concrete were 162 mm, 167 mm, 165 mm, 170 mm and 164 mm, respectively. Five wall panels and three 28-day interface specimens were poured and cured under the aforementioned conditions.

[0067] Two types of consolidation regions were observed in all three dried interface samples: consolidation regions at contact locations, adjacent consolidation regions separated by interparticle gaps, and interconnected interparticle pores leading to the interface treatment layer on the concrete side. After preparing positioning sections according to three-dimensional coordinates, it was confirmed that there was direct spatial connection between interconnected pores and the exposed surface of diatomaceous earth particles in all three independent samples.

[0068] Raman reference ranges were established for three 28-day interface specimens using the aforementioned Raman reference method. The peak positions of the main silicate characteristic bands of the first specimen ranged from 668 to 675 cm⁻¹. -1 and 963~978 cm -1 The second piece measures 670–676 cm. -1 and 962–979 cm -1 The third piece measures 669–675 cm. -1 and 964–978 cm -1 .

[0069] Fifteen fixed observation areas were tested according to the aforementioned unified Raman, BSE, and EDS testing sequence. A total of 13 observation areas met the criteria for determining a continuous hydrated calcium silicate region. Four, five, and four observation areas of the first to third 28-day interface specimens, respectively, met the criteria.

[0070] Example 3 Five batches of interface treatment slurry were prepared. Each batch contained 48.8 g of alkaline silica sol and 30.0 g of refined diatomaceous earth, resulting in 78.8 g of interface treatment slurry per batch. The dry solids mass of silica sol in each batch was 10.053 g, and the mass ratio of dry solids silica sol to refined diatomaceous earth was 0.335:1.

[0071] The actual mass of the interface treatment slurry used on the five insulation boards were 50.44 g, 50.73 g, 50.57 g, 50.81 g, and 50.39 g, respectively, corresponding to a wet coating weight of 140.1 g / m². 2 140.9 g / m 2 140.5 g / m 2 141.1 g / m 2 and 140.0 g / m 2 The solid load per unit area for silica sol drying was 17.87 g / m². 2 17.98 g / m 2 17.92 g / m 2 18.01 g / m 2 and 17.86 g / m 2 The unit area load of refined diatomaceous earth was 53.34 g / m². 2 53.65 g / m 2 53.48g / m 2 53.73 g / m 2 and 53.29 g / m 2 .

[0072] For each of the first to fifth batches of interface treatment slurry, one dry witness sample was prepared. For the first, second and third batches of interface treatment slurry, one dry interface sample and one 28-day interface specimen were prepared separately. Each synchronous sample was treated according to the measured wet coating amount per unit area of ​​the corresponding numbered wall panel insulation board.

[0073] The drying endpoints for the first to fifth drying witness samples were 26 h, 26 h, 28 h, 24 h and 26 h, respectively. In this embodiment, the drying endpoint was uniformly set at 28 h.

[0074] Five batches of cement-based concrete were mixed independently. The slump of the first to fifth batches of concrete were 165 mm, 168 mm, 163 mm, 172 mm and 166 mm, respectively. Five wall panels and three 28-day interface specimens were molded and cured under the aforementioned common conditions.

[0075] Two types of consolidation regions were observed in the three dried interface samples: consolidation regions at contact locations, adjacent consolidation regions separated by interparticle gaps, and interconnected interparticle pores leading to the concrete side. The interconnected pores were confirmed to be in direct contact with the exposed surface of the diatomaceous earth particles by positioning cross sections.

[0076] Raman reference ranges were established for three 28-day interface specimens using the aforementioned Raman reference method. The peak positions of the main silicate characteristic bands of the first specimen ranged from 668 to 675 cm⁻¹. -1 and 964–979 cm -1 The second piece measures 669–676 cm. -1 and 963~980 cm -1 The third piece measures 670–676 cm. -1 and 965–979 cm -1 .

[0077] The 15 fixed observation areas were tested according to the aforementioned unified testing sequence. Among them, 12 observation areas met the criteria for continuous hydrated calcium silicate area determination. The first to third specimens had 4, 3, and 5 observation areas that met the criteria, respectively.

[0078] Example 4 This embodiment uses another mineral source of diatomaceous earth, with a SiO2 mass fraction of 84.7%, a water content of 0.91%, a D10 of 9.1 μm, a D50 of 28.6 μm, a D90 of 62.4 μm, and a BET specific surface area of ​​27.5 m² / g. Phase detection was performed using a Cu target X-ray diffractometer. A broad diffuse peak corresponding to amorphous silica was observed in the range of 2θ of 20° to 30°, and a quartz diffraction peak was detected at the diffraction angle corresponding to crystalline quartz. Under a scanning electron microscope, an opening extending from the outer surface of the particle to the inside of the particle can be observed.

[0079] Five batches of interface treatment slurry were prepared. Each batch contained 40.0 g of alkaline silica sol and 30.0 g of diatomaceous earth as described in this example, resulting in 70.0 g of interface treatment slurry per batch. Each batch contained 8.24 g of dried silica sol solids, and the mass ratio of dried silica sol solids to diatomaceous earth was 0.275:1.

[0080] The actual mass of interface treatment slurry used on the five insulation boards were 44.71 g, 45.03 g, 44.86 g, 45.12 g, and 44.77 g, respectively, corresponding to a wet coating weight of 124.2 g / m². 2 125.1 g / m 2 124.6 g / m 2 125.3 g / m 2 and 124.4 g / m 2The solid load per unit area for silica sol drying was 14.62 g / m². 2 14.72 g / m 2 14.67 g / m 2 14.75 g / m 2 and 14.64 g / m 2 The load per unit area of ​​diatomaceous earth was 53.23 g / m². 2 53.61 g / m 2 53.40 g / m 2 53.71 g / m 2 and 53.30 g / m 2 .

[0081] For each of the first to fifth batches of interface treatment slurry, one dry witness sample was prepared. For the first, second and third batches of interface treatment slurry, one dry interface sample and one 28-day interface specimen were prepared separately. Each synchronous sample was treated according to the measured wet coating amount per unit area of ​​the corresponding numbered wall panel insulation board.

[0082] The drying endpoints for the first to fifth drying witness samples were 24 h, 26 h, 24 h, 26 h, and 26 h, respectively. In this embodiment, the drying endpoint was uniformly set at 26 h.

[0083] Five batches of cement-based concrete were mixed independently. The slump of the first to fifth batches of concrete were 166 mm, 163 mm, 170 mm, 167 mm and 169 mm, respectively. Five wall panels and three 28-day interface specimens were molded and cured under the aforementioned conditions.

[0084] In all three dried interface samples, two types of consolidation regions were observed at contact points: adjacent consolidation regions separated by interparticle gaps and interconnected interparticle pores leading to the concrete side. The interconnected pores were confirmed to be in direct contact with the exposed surface of the diatomite particles by positioning cross sections. Opening holes were observed in all three samples, and the three-dimensional reconstruction data confirmed the existence of a continuous path from the internal pores of the particles through the opening holes into the interconnected interparticle pores and continuing to the concrete side.

[0085] Raman reference ranges were established for three 28-day interface specimens using the aforementioned Raman reference method. The peak positions of the main silicate characteristic bands of the first specimen ranged from 669 to 676 cm⁻¹. -1 and 963~977 cm -1 The second piece is 670–677 cm. -1 and 962–978 cm -1 The third piece measures 669–675 cm. -1 and 964–978 cm -1 .

[0086] The positioning of the borehole walls and adjacent cavities of 14 open holes were completed in 3 28-day interface specimens. Among them, 11 open holes met the joint judgment criteria for calcium silicate hydrate in the borehole.

[0087] The 15 fixed observation areas were tested according to the aforementioned unified testing sequence. Among them, 13 observation areas met the criteria for continuous hydrated calcium silicate area determination. The first to third specimens had 4, 4, and 5 observation areas that met the criteria, respectively.

[0088] Example 5 Five batches of interface treatment slurry were prepared. Each batch contained 40.0 g of alkaline silica sol and 30.0 g of refined diatomaceous earth, resulting in 70.0 g of interface treatment slurry per batch. The dry solids content of silica sol in each batch was 8.24 g, and the mass ratio of dry solids of silica sol to refined diatomaceous earth was 0.275:1.

[0089] The actual mass of interface treatment slurry used on the five insulation boards were 44.86 g, 45.00 g, 44.75 g, 45.11 g, and 44.93 g, respectively, corresponding to a wet coating weight of 124.6 g / m². 2 125.0 g / m 2 124.3 g / m 2 125.3 g / m 2 and 124.8 g / m 2 The solid load per unit area for silica sol drying was 14.67 g / m². 2 14.71 g / m 2 14.63 g / m 2 14.75 g / m 2 and 14.69 g / m 2 The unit area load of refined diatomaceous earth was 53.40 g / m². 2 53.57 g / m 2 53.27g / m 2 53.70 g / m 2 and 53.49 g / m 2 .

[0090] For each of the first to fifth batches of interface treatment slurry, one dry witness sample was prepared. For the first, second, and third batches of interface treatment slurry, one interface sample was prepared before storage and after drying, one interface sample was prepared after storage and transportation and after drying, and one interface specimen was prepared at 28 days. The sample before storage and the sample after storage and transportation were matched samples prepared independently using the same numbered slurry. All synchronous samples were treated according to the measured wet coating amount per unit area of ​​the corresponding numbered wall panel insulation board.

[0091] The drying endpoints for the first to fifth drying witness samples were 24 h, 26 h, 24 h, 26 h and 24 h, respectively. In this embodiment, the drying endpoint was uniformly set at 26 h.

[0092] After reaching the uniform drying endpoint of 26 h, the three interface samples dried before storage were directly used for interface structure testing. The remaining five wall panel insulation boards, three interface samples dried after storage and transportation, and three 28-day interface specimens were stored in an indoor environment at 22±3 ℃ and relative humidity of 45%~65% for 7 days. The wall panel insulation boards and specimens were placed horizontally on a flat bracket with the interface treatment surface facing upwards. Adjacent boards were separated by pads placed around the perimeter of the boards that did not contact the interface treatment surface.

[0093] After 7 days of storage, 5 wall panel insulation boards, 3 interface samples after storage and transportation and drying, and 3 28-day interface specimens were fixed with transport brackets and loaded into a closed van. The 42 km road transport was completed in 68 minutes. Within 2 hours after the transport was completed, the wall panel formwork and the 28-day interface specimens were poured with concrete.

[0094] Two types of consolidation portions and adjacent consolidation portions separated by particle gaps were observed in the three dried interface samples before and after storage and transportation. In the three independent samples after storage and transportation, the particles could be continuously traced from the interface treatment layer towards the concrete side into the interior of the diatomite particle layer, and the interconnected pores were confirmed to be in direct contact with the exposed surface of the diatomite particles through positioning sections.

[0095] Five batches of cement-based concrete were mixed independently. The slump of the first to fifth batches of concrete were 163 mm, 168 mm, 166 mm, 170 mm and 165 mm, respectively. The first to fifth wall panel insulation boards, which had undergone 7 days of storage and 42 km of transportation, were laid, poured and vibrated. The first to third batches of concrete were used for the corresponding 28-day interface specimens that had undergone the same storage and transportation process. The wall panels and interface specimens were cured for 28 days.

[0096] Raman reference ranges were established for three 28-day interface specimens using the aforementioned Raman reference method. The peak positions of the main silicate characteristic bands of the first specimen ranged from 668 to 675 cm⁻¹. -1 and 963~978 cm -1 The second piece measures 669–676 cm. -1 and 962–979 cm -1 The third piece measures 668–676 cm. -1 and 964–979 cm -1 .

[0097] The 15 fixed observation areas of the three 28-day interface specimens were tested according to the aforementioned unified testing sequence. Among them, 13 observation areas met the joint judgment condition of continuous hydrated calcium silicate between the particle contact area, the diatomaceous earth particle surface area and the cement paste area. The first to third specimens had 4, 5 and 4 observation areas respectively that met the conditions.

[0098] Comparative Example 1 This comparative example sets up comparative conditions with reference to the single interface agent wet construction conditions disclosed in CN101424115A. Molded polystyrene foam boards of the same specifications as in Example 1 are used. An interface agent composed of water-soluble adhesive, water and SiO2 ultrafine powder is applied to the concrete contact surface of the board, and cement-based concrete is poured while the interface agent is kept moist.

[0099] The water-soluble adhesive used is a polyacrylate emulsion with a solid mass fraction of 50.1%; the SiO2 ultrafine powder used is diatomaceous earth that has undergone air jet milling and classification, with a D10 of 0.27 μm, a D50 of 0.73 μm, a D90 of 1.41 μm, and a D99 of 1.86 μm; the mass of the water-soluble adhesive in the interface agent formulation is calculated based on the mass of the polyacrylate emulsion stock solution.

[0100] Five batches of interface agent were prepared. For each batch, 80.0 g of polyacrylate emulsion, 160.0 g of water, and 40.0 g of ultrafine diatomaceous earth were weighed. First, the polyacrylate emulsion was added to the water and mechanically stirred. After the mixture was homogeneous, the ultrafine diatomaceous earth was gradually added while stirring continuously. Stirring continued until no visible dry powder agglomerates were found in the interface agent. Each batch yielded 280.0 g of interface agent. Based on the mass of the polyacrylate emulsion stock solution, the mass ratio of water-soluble adhesive:water:cement:water-retaining agent:ultrafine powder was 1:2:0:0:0.5.

[0101] Five molded polystyrene foam boards were taken, and their concrete contact surfaces were cleaned according to the aforementioned common conditions. Each board was then treated with the first to fifth batches of interface agent. A short-nap roller was used to apply the agent first along the length of the insulation board, then along its width, ensuring the interface agent covered the entire concrete contact surface. The actual interface agent used on the first to fifth insulation boards were 194.8 g, 196.2 g, 195.4 g, 197.0 g, and 195.7 g, respectively, corresponding to a wet coating weight of 541.1 g / m². 2 545.0 g / m 2 542.8 g / m 2 547.2 g / m 2 and 543.6 g / m 2 .

[0102] For each of the first, second, and third batches of interface agents, a separate 28-day interface specimen was prepared. The interface treatment surface of each 28-day interface specimen was treated according to the measured wet coating amount per unit area of ​​the wall panel insulation board with the same number.

[0103] This comparative example does not set a drying endpoint for the interface agent. After the interface agent is applied, the interface treatment surface is kept horizontal and facing upwards. After the cement-based concrete with the same number is mixed, it is poured directly.

[0104] Five batches of cement-based concrete with the same mix proportion and mixing method as in Example 1 were prepared independently. The slump of the first to fifth batches of concrete were 165 mm, 168 mm, 164 mm, 170 mm and 166 mm, respectively. The time from the completion of the interface agent coating to the start of concrete pouring was 18 min, 20 min, 19 min, 21 min and 20 min, respectively. At the start of pouring, the interface agent surface of the five insulation boards remained continuously moist, and the interface agent did not dry out completely.

[0105] Five insulation boards treated with the interface agent were laid on a 600 mm × 600 mm mold, with the interface agent-treated side facing the concrete pouring side. A 100 mm thick layer of cement-based concrete of the corresponding batch was poured on the interface agent side and compacted with a vibrating table for 30 seconds. The first to third batches of cement-based concrete were used for 28-day interface specimens with the same number. The wall panels and 28-day interface specimens were demolded after curing in the mold for 48 hours and continued to be cured in an environment with a temperature of 20 ± 2 ℃ and a relative humidity of not less than 95% for 28 days.

[0106] This comparative example was completed with concrete pouring in a moist interface agent state. Before pouring, the same dry diatomaceous earth particle interface treatment layer as in Examples 1-5 was not formed. Therefore, the solidified part, adjacent solidified parts separated by particle gaps, exposed surface area in the dry state, interconnected interparticle pores in the dry state, and spatial connection between open pores and interparticle pores in the dry state are not applicable to this comparative example.

[0107] To detect the interface hydration state after curing, a 250 μm × 200 μm observation area was set at 20%, 35%, 50%, 65%, and 80% of the effective interface length on each 28-day interface specimen, forming a total of 15 observation areas on the three independent specimens. In each observation area, Raman positioning detection was first performed on the interface agent adjacency area and the cement paste area, and the coordinates were saved. Subsequently, SEM secondary electron imaging, BSE imaging, and EDS surface scanning were performed, and the corresponding detection results were based on the saved coordinates.

[0108] When solid hydration products can be continuously tracked in the BSE image from the interface agent adjacency region to the cement paste region, and EDS shows that Ca and Si are co-distributed on the corresponding path, and the main silicate characteristic spectral peaks of the two Raman positioning positions in the interface agent adjacency region and the cement paste region both fall within the Raman reference range of the specimen, the observed region is recorded as a cross-interface continuous hydration product region.

[0109] According to the above method, four, four and four observation areas of the first to third 28-day interface specimens respectively met the judgment criteria, and 12 of the 15 observation areas were recorded as cross-interface continuous hydration product areas.

[0110] Comparative Example 2 This comparative example uses the same molded polystyrene foam board, refined diatomaceous earth, and alkaline silica sol as Example 1. The first stage of treatment is completed according to the interface treatment composition and operation method of Example 1. After the first stage interface treatment layer reaches the drying endpoint, the same alkaline silica sol without diatomaceous earth is coated again on the side of the first stage interface treatment layer facing the concrete, so that the second stage silica sol covers the entire first stage interface treatment surface, and then it is dried again.

[0111] Five batches of first-stage interface treatment slurry were prepared. For each batch, 40.0 g of alkaline silica sol and 30.0 g of refined diatomaceous earth were taken and dispersed and allowed to stand under the aforementioned common conditions. Each batch yielded 70.0 g of first-stage interface treatment slurry. The dry solids of silica sol contained in each batch were 8.24 g, and the mass ratio of dry solids of silica sol to refined diatomaceous earth was 0.275:1.

[0112] Five molded polystyrene foam boards were coated with the first-stage interface treatment slurry from batches 1 to 5, respectively. The actual slurry usage was 44.95 g, 45.12 g, 44.83 g, 45.06 g, and 44.91 g, corresponding to wet coating amounts of 124.9 g / m². 2 125.3 g / m 2 124.5 g / m 2 125.2 g / m 2 and 124.8 g / m 2 The solid load per unit area for silica sol drying was 14.70 g / m². 2 14.75 g / m 2 14.66 g / m 2 14.73 g / m 2 and 14.68 g / m 2 The unit area load of refined diatomaceous earth was 53.51 g / m². 2 53.71 g / m 253.37 g / m 2 53.64 g / m 2 and 53.46g / m 2 .

[0113] For each of the first-stage interface treatment slurries of batches 1 to 5, one first-stage drying witness sample was prepared. For each of the first, second, and third batches of first-stage interface treatment slurries, one dried interface sample and one 28-day interface specimen were prepared separately. The first-stage interface treatment surface of each synchronous sample was treated according to the measured wet coating amount per unit area of ​​the wall insulation board with the same number.

[0114] After the first stage coating is completed, the samples are naturally dried under the aforementioned common conditions. The drying endpoints of the first stage drying witness samples 1 to 5 are 24 h, 26 h, 24 h, 26 h and 24 h, respectively, with 26 h as the unified drying endpoint of the first stage.

[0115] After the first stage reaches a uniform drying endpoint of 26 hours, the same alkaline silica sol is applied to the first-stage interface treatment surfaces of five wall panel insulation boards, corresponding dried interface samples, and 28-day interface specimens using a short-nails roller. The coating is first applied along the length direction and then along the width direction. No diatomaceous earth is added in the second stage. The mass of silica sol used in the second stage for each synchronous sample is calculated based on its actual treated area and the measured wet coating amount per unit area of ​​the second stage for wall panel insulation boards with the same number.

[0116] The actual silica sol used in the second stage for the insulation boards of the first to fifth wall panels were 39.82 g, 40.06 g, 39.91 g, 40.14 g, and 39.87 g, respectively, corresponding to a wet coating amount of 110.6 g / m². 2 111.3 g / m 2 110.9 g / m 2 111.5 g / m 2 and 110.8 g / m 2 The additional solid load per unit area for the second stage of silica sol drying was 22.79 g / m². 2 22.92 g / m 2 22.84 g / m 2 22.97 g / m 2 and 22.81 g / m 2 The combined solid load per unit area for the two stages of silica sol drying was 37.49 g / m². 2 37.67 g / m 2 37.50 g / m 2 37.70 g / m 2and 37.49 g / m 2 .

[0117] After the second stage coating was completed, the samples were allowed to dry naturally in an environment with a temperature of 25±2 ℃ and a relative humidity of 52±5%. The drying endpoint of the second stage was determined by five witness samples that had undergone the same two-stage treatment. The drying endpoints of the first to fifth witness samples were 34 h, 36 h, 34 h, 36 h and 34 h, respectively. 36 h was taken as the unified drying endpoint of the second stage.

[0118] Five batches of cement-based concrete with the same mix proportions and mixing methods as in Example 1 were prepared independently. The slump of the first to fifth batches of concrete were 164 mm, 167 mm, 165 mm, 169 mm and 166 mm, respectively. The five wall panel insulation boards that reached the unified drying endpoint of the second stage after 36 hours were laid on the mold platform. A 100 mm thick layer of cement-based concrete of the corresponding batch was poured on one side of the second stage treatment surface and vibrated for 30 seconds. The first to third batches of concrete were used for the same numbered 28-day interface specimens. The wall panels and interface specimens were cured for 28 days under the aforementioned common conditions.

[0119] Three dried interface samples after two-stage treatment were subjected to SEM secondary electron imaging and BSE imaging. In all three samples, the consolidation area at the contact position of diatomite particles could be identified, and the solid covering was observed to span the non-contact area between adjacent diatomite particles and connect the consolidation areas at different particle contact positions. In some observation areas, the particle gaps and the exposed surface of diatomite particles could still be identified.

[0120] In the old draft, 13 out of 15 fixed regions of the three specimens had been recorded as having continuous cladding, which can provide the original basis for the above structural facts.

[0121] X-ray microtomography was performed on three dried interface samples. In the three-dimensional reconstruction data, the interparticle pore path from the interface treatment layer towards the concrete side into the diatomite particle layer could still be observed. In the positioning section, some continuous solid covering material could be observed between the interparticle pores and the surface of the diatomite particles, so that the interparticle pores at the corresponding positions did not directly reach the exposed surface of the diatomite particles.

[0122] Open pores were still observed on the diatomite particles in the three dried interface samples, and the three-dimensional reconstruction data confirmed the existence of open pores that enter the interparticle pores from the internal pores of the particles through the pore openings and lead to the interface treatment layer facing the concrete side.

[0123] Calcium silicate hydrate in the openings of three 28-day interface specimens was detected. Raman localization was first performed on the openings where the orifice, wall and adjacent cavity could be continuously identified and the coordinates were saved. Then BSE imaging and EDS detection were performed at the same coordinates. Five openings were detected in each of the first to third specimens. Two, three and two openings respectively met the conditions of solid hydration products, co-distribution of Ca and Si and Raman reference range. Calcium silicate hydrate was recorded in 7 out of a total of 15 openings.

[0124] Three 28-day interface specimens were tested according to the aforementioned continuous hydrated calcium silicate area detection method. For each fixed observation area, Raman positioning of three locations—the particle contact area, the diatomaceous earth particle surface area, and the cement paste area—was completed and the coordinates were saved. Then, BSE imaging and EDS surface scanning were performed. The joint judgment was completed based on the saved coordinates.

[0125] Of the 1st to 3rd 28-day interface specimens, 3, 2, and 3 observation areas respectively met the criteria for determining a continuous hydrated calcium silicate region. Among the 15 fixed observation areas, 8 were recorded as continuous hydrated calcium silicate regions.

[0126] Table 1. Main interface processing conditions for each embodiment and comparative example Group Interface processing conditions Mass ratio of dried silica sol solids to diatomaceous earth Solid load per unit area of ​​silica sol drying Pre-pouring state Example 1 First-source diatomaceous earth + alkaline silica sol 0.275∶1 14.65~14.77 g / m² Dry for 26 hours Example 2 First-source diatomaceous earth + alkaline silica sol 0.220∶1 11.72~11.80 g / m² Dry for 24 hours Example 3 First-source diatomaceous earth + alkaline silica sol 0.335∶1 17.86~18.01 g / m² Dry for 28 hours Example 4 Secondary mineral source: diatomaceous earth + alkaline silica sol 0.275∶1 14.62~14.75 g / m² Dry for 26 hours Example 5 Same as Example 1 0.275∶1 14.63~14.75 g / m² After drying, store for 7 days and transport for 42 km. Comparative Example 1 Polyacrylate emulsion, water and ultrafine diatomaceous earth wet interface agent not applicable not applicable Pouring in a moist state Comparative Example 2 The first stage is the same as in Example 1, and the second stage involves continuous coating with the same alkaline silica sol. Phase 1: 0.275:1 The total concentration of the two stages was 37.49–37.70 g / m². After the second stage of drying for 36 hours, pouring is carried out. Table 2. Core interface structure and 28-day hydration results of each embodiment and comparative example. Group Two types of contact locations consolidation parts Adjacent consolidated portions separated by interparticle gaps Intergranular pores leading to the concrete side The connecting pores are directly connected to the exposed surface. Openings connecting to the concrete side Calcium silicate hydrate in the opening Continuous hydrated calcium silicate region Example 1 exist exist exist All 3 independent samples were confirmed exist 12 / 14 14 / 15 Example 2 exist exist exist All 3 independent samples were confirmed Not detected Not detected 13 / 15 Example 3 exist exist exist All 3 independent samples were confirmed Not detected Not detected 12 / 15 Example 4 exist exist exist All 3 independent samples were confirmed exist 11 / 14 13 / 15 Example 5 Existing after storage and transportation Existing after storage and transportation Existing after storage and transportation All three independent samples were confirmed after storage and transportation. Not detected Not detected 13 / 15 Comparative Example 1 not applicable not applicable not applicable not applicable not applicable not applicable Not applicable¹ Comparative Example 2 Recognizable Localized presence, along with continuous solid-state coverage spanning non-contact areas of particles. exist Some locations are separated by a continuous solid covering. exist 7 / 15 8 / 15 Comparative Example 1 used a wet interface agent to directly pour concrete, and did not form the same dry diatomaceous earth particle interface structure as Examples 1-5. Therefore, it is not applicable to the determination of the continuous hydration calcium silicate path in the particle contact area, diatomaceous earth particle surface area, and cement paste area. When the cross-interface continuous hydration product determination method corresponding to Comparative Example 1 was used for detection, 12 out of 15 observation areas met the determination conditions.

[0127] Examples 1-3 used diatomaceous earth from the same mineral source and changed the mass ratio of the dried silica sol solid to the diatomaceous earth. In the dried interfaces of the three examples, two types of consolidation parts were observed at the contact positions, adjacent consolidation parts separated by particle gaps, and interconnected interparticle pores leading to the concrete side. The interconnected pores and the exposed surface of the diatomaceous earth particles were directly connected by positioning cross sections in all three independent dried interface samples. In the 28-day interface specimens, hydrated calcium silicate was detected from the particle contact area through the diatomaceous earth particle surface area to the cement paste area.

[0128] Example 4 uses diatomaceous earth from a second mineral source. After drying, the interface also shows two types of consolidation at contact points, interparticle gaps, interparticle pores, and open pores communicating with the concrete side. In the 28-day interface specimen, hydrated calcium silicate and continuous hydrated calcium silicate regions were detected in the open pores. After drying, the insulation board of Example 5 was stored for 7 days and transported by road for 42km. The three dried interface specimens after storage and transportation still confirmed the two types of consolidation at contact points, interparticle gaps, interparticle pores, and direct spatial connection between the communicating pores and the exposed surface of the diatomaceous earth particles.

[0129] Comparative Example 1: Cement-based concrete was directly poured in a moist interface agent state, and no interface state was formed before pouring for the drying interface structure detection of Examples 1-5. Comparative Example 2: After the diatomite particle interface treatment layer in the first stage dried, the same alkaline silica sol was continued to be coated. After drying, a continuous solid cover across the non-contact area of ​​adjacent diatomite particles could be observed in the interface. In some locations, the continuous solid cover was observed to be located between the pores between particles and the surface of diatomite particles. The detection results of the hydrated calcium silicate and the continuous hydrated calcium silicate area in the open pores after 28 days are listed in Table 2.

[0130] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A molding process for thermal insulation material concrete wall panels, characterized in that, include: Diatomaceous earth particles containing amorphous silica phase are added to an alkaline colloidal silica aqueous dispersion for dispersion to obtain an interface treatment slurry. An interface treatment slurry is applied to the concrete contact surface of a molded polystyrene foam board and dried to obtain an insulation board with an interface treatment layer. The interface treatment layer contains a solidified portion at the contact point between diatomaceous earth particles and the surface of the insulation board, as well as a solidified portion at the contact point between adjacent diatomaceous earth particles, and adjacent solidified portions separated by particle gaps. The interface treatment layer has interconnecting pores formed by particle gaps and leading to the concrete-facing side of the interface treatment layer. The interface treatment layer also contains exposed surface areas of diatomaceous earth particles that are directly connected to the interconnecting pores. The insulation board with the interface treatment layer is laid on the formwork, with the interface treatment layer facing the concrete pouring side, and cement-based concrete is poured on the side of the interface treatment layer. After the wall panel is poured, it is cured in the formwork and then cured again after demolding. The interface treatment layer after curing contains a region of hydrated calcium silicate that is in continuous contact with the hydration products of cement paste in cement-based concrete, thus obtaining a thermal insulation concrete wall panel.

2. The molding process for thermal insulation material concrete wall panels according to claim 1, characterized in that, The dried interface treatment layer contains open pores on the diatomaceous earth particles. These open pores are connected to the outer surface of the particles, and their openings remain open, leading to the side of the interface treatment layer facing the concrete through the connecting pores.

3. The molding process for thermal insulation material concrete wall panels according to claim 2, characterized in that, In the cured interface treatment layer, there are open pores of hydrated calcium silicate distributed on the surface of the pore wall and in the adjacent pore cavity.

4. The molding process for thermal insulation material concrete wall panels according to claim 1, characterized in that, The contact portion contains a liquid bridge observed during the drying process, and a solidified portion is observed at the original liquid bridge location after the drying endpoint is reached.

5. The molding process for thermal insulation material concrete wall panels according to claim 1, characterized in that, The interface treatment slurry is composed of diatomaceous earth particles and an alkaline colloidal silica aqueous dispersion.

6. The molding process for thermal insulation material concrete wall panels according to claim 1, characterized in that, After curing, there is a continuous hydrated calcium silicate region between the interface treatment layer and the cement paste of the cement-based concrete. The continuous hydrated calcium silicate region is distributed sequentially in the contact area between the diatomite particles and the surface of the insulation board or the contact area between adjacent diatomite particles, the surface area of ​​the diatomite particles and the cement paste area of ​​the cement-based concrete, and the hydrated calcium silicate in the above adjacent areas is in continuous contact with each other.

7. The molding process for thermal insulation material concrete wall panels according to claim 1, characterized in that, The coating and drying of the interface treatment slurry are completed before the insulation board enters the wall panel forming mold. After the insulation board is dried, it is stored and transported and then laid on the wall panel forming mold. Cement-based concrete is poured on one side of the interface treatment layer and cured.

Citation Information

Patent Citations

  • Construction method for interface adhesive for plastering, preventing crack and increasing adhesive intensity of plastering and facing

    CN101424115A